Spatiotemporal distribution of benthic communities in Belawan Estuary, Indonesia - AHMAD MUHTADI; RUSDI LEIDONALD; AMANATUL FADHILAH; FEBRIYANTI SIMANJUNTAK; SALMA BEGUM (Society for Indonesian Biodiversity, 2025)
Abstract. Muhtadi A, Leidonald R, Fadhilah A, Simanjuntak F, Begum S. 2025. Spatiotemporal distribution of benthic communities in Belawan Estuary, Indonesia. Biodiversitas 26: 5556-5566. The Belawan River predominantly influences the hydrodynamics of the Belawan Estuary, Indonesia, and the tidal currents from the Strait of Malacca are a dynamic ecosystem with high ecological variability. This study examined the spatiotemporal variations in the macro-benthic community structure in the Belawan Estuary in October 2023, North Sumatra Province, Indonesia. Benthic samples were collected from eight points representing the upstream, middle, and downstream areas of the estuary, using an Ekman grab during high and low tides, with three replicates each. Sampling and water quality measurements were conducted four times in accordance with the tidal cycle: during the new moon, first quarter, full moon, and last quarter. Benthic community structure analysis, Principal Component Analysis (PCA) tests correlating water quality with benthic density and diversity, and the Kruskal-Wallis tests with Dunn's post hoc tests were conducted. A total of 36 species were identified, dominated by Mollusks. The polychaete Nereis virens was ubiquitous, while the highest densities were of invasive bivalves Mytilopsis sallei (average 133 individuals. m-² ±159.76) and Dreissena polymorpha (average 199 individuals. m-² ±525.51). Principal component analysis indicated that tidal dynamics explained more than 70% of community variation. These findings demonstrate that tides play a critical role in structuring benthic assemblages in the Belawan Estuary and provide essential baseline data for managing estuarine biodiversity under increasing anthropogenic pressure.